If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 3) = 1 + 4x Reorder the terms: 2(3 + x) = 1 + 4x (3 * 2 + x * 2) = 1 + 4x (6 + 2x) = 1 + 4x Solving 6 + 2x = 1 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6 + 2x + -4x = 1 + 4x + -4x Combine like terms: 2x + -4x = -2x 6 + -2x = 1 + 4x + -4x Combine like terms: 4x + -4x = 0 6 + -2x = 1 + 0 6 + -2x = 1 Add '-6' to each side of the equation. 6 + -6 + -2x = 1 + -6 Combine like terms: 6 + -6 = 0 0 + -2x = 1 + -6 -2x = 1 + -6 Combine like terms: 1 + -6 = -5 -2x = -5 Divide each side by '-2'. x = 2.5 Simplifying x = 2.5
| 8(-3x+1)=-10(x-4)-14x | | 0.5x-6=-24 | | 2x^2+16x+42=10 | | 3(3x+13)=9x-8 | | (x+31)-5=3x | | 46.17=x+0.15x+0.065x | | 1.8q=3.24 | | 2X-3X+7Z=9 | | 6(x-3)=3(3x-2) | | 2=(3x+4)(1-x) | | 20=14-6 | | 7log(x)=32 | | E(x)=lx-1l+lx+3l | | 1.8+7s=9.1 | | 9.25t+9=15.5t+14 | | (3x-6)+27=-15 | | Y=-2x^2-13x+7 | | -4/5-9=1 | | -4/5-6=4 | | 6m+10=2 | | 3x-11=2x-(5-x) | | 6x(3x-2)(x+7)=0 | | 7(2x-3)-4(x+5)=8(x-1)+5 | | 5+4(w+2)=(w+7)+1 | | 8s^2+14s=15 | | 5x=21-x | | 5x=21+x | | 4x-4=-12+10 | | m=2(12w-19) | | -3*(p/16-3p) | | m=12w-19 | | 2x-12x=-3+1 |